Asuhan Kebidanan Pada Masa Kehamilan, Persalinan, Nifas, Bbl, Kb Dan Gambaran Pengetahuan Kehamilan Pada Ny. K Di Klinik Pratama Kita Kecamatan Berastagi Kab. Karo Tahun 2022 - Nazri Nasution (JURNAL RISET RUMPUN ILMU KESEHATAN, 2023)
High maternal and infant mortality rates are a major health problem in Indonesia. The author contributes by providing comprehensive midwifery care for pregnancy, maternity, postpartum, newborns, and family planning to promote better health. The author has provided direct midwifery care and has real experience. An observational case study was conducted at the Pratama Kita Clinic, Kec. Berastagi from February to June 2016. to provide comprehensive care to Mrs. K, who is 36 years old, experienced pregnancy, childbirth, postpartum, newborn and caesarean section. Interviews, observations, examinations and documentation are used to collect data. Case study analysis is used to transform data into easy-to-understand information. After Mrs. K started pregnant in the third trimester, the author implemented and provided comprehensive midwifery care.